Change in Probiotic Microflora and Physico-chemical Characteristics of Rose Hip Marmalade Bio-yoghurts During Refrigerated Storage - GURSES, MUSTAFA; CETIN, BULENT; SENGUL, MUSTAFA (Asian Journal of Chemistry, 2010)
Yoghurt, produced by adding rose hip marmaleda and L. acidophilus, was stored for 15 d at 4 ± 1 °C and changes in selected microbiological and physicochemical parameters were monitored during storage. Ascorbic acid and pH values of yoghurt samples decreased during storage. There were minimal differences in the aerobic mesophilic bacteria counts among yoghurt types. S. thermophilus counts of yoghurt samples similarly decreased with concentration of ascorbic acid (p < 0.05) and L. bulgaricus count (p < 0.01). The alteration in L. bulgaricus counts of yoghurt samples was similar to S. thermophilus. L. acidophilus L. bulgaricus and S. thermophilus counts ranged in 7.21, 7.19, 5.41 and 2.01, 9.83, 6.97 log cfu g-1, respectively. Fruit, storage period and ascorbic acid importantly affected on the viable counts of L. acidophilus (p < 0.01). Coliform, S. aureus, yeast and mould were not determined any yoghurt samples during the storage period of 15 d. Probiotic culture count decreased under the level of 106 cfu/g after 6 d.